Self-Efficacy of Teachers Working in Mainstream Schools – Research Communication - Nowak, Beata Maria (Przegląd Badań Edukacyjnych (Educational Studies Review), 2021)
This article presents the results of a study on the self-efficacy of teachers working at mainstream schools and the results of intergroup analyses (mainstream school teachers versus special education teachers), being part of a research project focused on identifying the determinants of teachers’ sense of self-efficacy. Intergroup comparisons were made due to assumed differences in the self-efficacy of teachers in mainstream and special schools, resulting from the specific organisation and functioning of the two types of schools and the differentiated actors. The theoretical basis was the social learning theory of A. Bandura. The research was conducted with the use of the “Sense of Efficacy Test” by M. Chomczyńska-Rubacha and K. Rubacha. A total of 801 teachers took part in the study, including 442 teachers from mainstream schools and 359 from special schools (special education centres – SOWs; youth sociotherapy centres – MOSs; youth education centres – MOWs; prisons – ZKs). Research analyses have shown that the sense of self-efficacy in teachers from mainstream schools is dependent on their place of residence – increasing along with its size. Cognitive and action resources are determined by the level of education of the mothers of the studied teachers, while motivational resources are determined by the type of school at which they work. A cluster analysis identified two independent groups of teachers – those scoring high and those scoring low in terms of self-efficacy. A model mismatched with the data was obtained, which means that on the basis of sociodemographic variables and other information about teachers (education level of their parents, type of school) it is not possible to predict their assignment unambiguously to the distinguished groups. In terms of intergroup analyses, a higher sense of self-efficacy and greater motivational and cognitive-action resources were noted in teachers from mainstream schools than in teachers from special schools. The place of work of teachers from both compared groups significantly differentiates their sense of self-efficacy and the level of motivational as well as cognitive-activity resources (teachers employed at a lower secondary school possess more motivational resources, compared to teachers employed in special education centres). In turn, teachers employed at prisons are characterised by a higher level of cognitive-activity resources compared to teachers employed at secondary schools and youth sociotherapeutic and educational centres.